Podjetniško premoženje zakoncev po Družinskem zakoniku - Dugar, Gregor (Pravnik, 2014)
The Marriage and Family Relations Act was created during the collective ownership period, when entrepreneurship was not yet developed in Slovenia. After Slovenia's independence in 1991 and the adoption of a new constitutional arrangement, entrepreneurship began rapidly developing. Since the very beginning, entrepreneurship has been in the domain of not only unmarried people, but also spouses. The property of some spouses increases significantly thanks to being involved in entrepreneurship. In these cases, an equity stake in a company usually represents the largest part of common property of the spouses. With regard to the property relations between the spouses, the Marriage and Family Relations Act does not define any special rules concerning spouses' equity stake in a company. The new Family Code, which was rejected on referendum in 2012, includes two new provisions about the property relations between the spouses about their participation in a company. The Author analyses the accordance of these two provisions with other provisions of family law about property relations between spouses and presents his view of the regulation of the property relations between the spouses about their participation in a company.
Keywords: lastnina; marriage; podjetja; premoženje; razmerja; zakonska zveza